K'96 : International Ceramic Art. - Altarriba, Antonio (S.l. : South Carelian Art Museum, 1996)
Cragg, Tony ; Garraza, Angel ; Gryta, Radoslaw ; Kaneko, Jun ; Toubes, Xavier
K'96 International Ceramic Art, South Carelian Art Museum, Lappeenranta, 15 06 - 01 09 1996
boek